PROGRAM SIMULASI KOMPUTER UNTUK MENINGKATKAN RENDEMEN PENGGERGAJIAN - Osly Rachman (Jurnal Penelitian Hasil Hutan, 1994)
The computer simulation programs for increasing lumber recovery are presented  in this paper.  These programs  were created for sawing logs with live sawing,  half sawing, and semi-quarter  sawing patterns, and convening  the sawn limber into blanks using turbo basic language version  1, 1.  The log model used was a truncated cylinder to represent the real logs.The  best opening  first (BOF) of logs is computed  by entering data of log factors such as diameter  and  length,  and sawing factors such as saw kerf, sawn limber thickness, allowance for sawing thickness, blank width, and allowance for sawing width.For several runs on computer under any circumtances  the program produced nominal lumber and blank recovery ranging 73-76 %  and 83 - 89 %, respectively, the values of shrinkage allowance,  planing allowance and sawing  variation have been  included in nominal lumber recovery.